If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(10) + -3w = 5(15 + -4w) Multiply 7 * 10 70 + -3w = 5(15 + -4w) 70 + -3w = (15 * 5 + -4w * 5) 70 + -3w = (75 + -20w) Solving 70 + -3w = 75 + -20w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '20w' to each side of the equation. 70 + -3w + 20w = 75 + -20w + 20w Combine like terms: -3w + 20w = 17w 70 + 17w = 75 + -20w + 20w Combine like terms: -20w + 20w = 0 70 + 17w = 75 + 0 70 + 17w = 75 Add '-70' to each side of the equation. 70 + -70 + 17w = 75 + -70 Combine like terms: 70 + -70 = 0 0 + 17w = 75 + -70 17w = 75 + -70 Combine like terms: 75 + -70 = 5 17w = 5 Divide each side by '17'. w = 0.2941176471 Simplifying w = 0.2941176471
| x(3x-2)+x(4x-2)=(7x+8)(x-4) | | -7+5m+6=-27 | | 3(2x+7)=7-2(x-7) | | 3-10(x)=127 | | 2r+2=-3r-5+5 | | 4/3*3.14*5^3 | | n+14=6 | | -5k-3=-33 | | f(x)=3x-1/x^3 | | 3x-7x+8=2/3 | | y=140/x | | (x-8)(x-8)-1=0 | | -0.28p-0.06(2-6p)=0.06(p-2)-0.1 | | f(x)=5x^4+3x+7 | | 12,000/52=x/1 | | 104+8x=107+7x | | 79+9x=94+4x | | 2(6+-7x+2x^2)=0 | | 10-.33333y=4+6x | | 9q^2+9q-10=0 | | 49=7j | | 4+5w-4w=4-2 | | z-7=36 | | 2-(1/4) | | (5x)+(x+20)+(2x)=180 | | 4+9(x)=184 | | (9*sqr-1)8(-6*sqr-4)= | | 20=x-4 | | w-50=16 | | -14=(6/7)x-4-7x | | (9*((-1)^1/2)*((-6)((-4)^1/2))= | | 6x-7=1+4x |